2017
DOI: 10.1002/jcp.26224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mono‐(2‐ethylhexyl) phthalate (MEHP) on proliferation of and steroid hormone synthesis in rat ovarian granulosa cells in vitro

Abstract: This study aimed to examine the proliferation of and secretion by rat ovarian granulosa cells (GCs) treated with mono-(2-ethylhexyl) phthalate (MEHP). Ovarian GCs were incubated with MEHP at concentration of 0, 25, 50, 100, and 200 µM for 24 hr. Cell viability was determined using the MTT Cell Proliferation Assay. Progesterone and estradiol production was evaluated by radioimmunoassay (RIA) and the expression of FSHR, PR, and ER was measured by immunocytochemistry. StAR, P450scc, 3β-HSD, 17β-HSD, and P arom mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…The expressions of StAR and P450scc were lower after exposure to MnBP (Figure 6). These results are similar to those of the exposure of MEHP in rat ovarian granulosa cells and the exposure of DBP in human granulosa cells at low dose [45,48].…”
Section: Effect Of Mnbp On Amh Inhibin B Star and P450ssc Expressionsupporting
confidence: 86%
See 1 more Smart Citation
“…The expressions of StAR and P450scc were lower after exposure to MnBP (Figure 6). These results are similar to those of the exposure of MEHP in rat ovarian granulosa cells and the exposure of DBP in human granulosa cells at low dose [45,48].…”
Section: Effect Of Mnbp On Amh Inhibin B Star and P450ssc Expressionsupporting
confidence: 86%
“…Several reports have shown that phthalate metabolites may affect the granulosa cells. In rat granulosa cells, MEHP suppresses aromatase transcript levels, estradiol production, steroid hormone synthesis, and key enzymes in progesterone production, and causes the attenuation of cell proliferation and induction of apoptosis [16,44,45]. These results suggest that MEHP has important effects on rodent granulosa cells, but there is no information in humans.…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have shown that environmental endocrine-disrupting chemicals (EDCs) can affect steroidogenesis in GCs [24,25]. Bisphenol A (BPA), a chemical widely used for the production of epoxy resins and polycarbonate plastics, was found to be an important environmental EDC.…”
Section: Research Highlightmentioning
confidence: 99%
“…It induced ovarian toxicity by inhibition of follicular development and abnormal steroid hormone synthesis in cultured rat ovarian follicles 85 . It also inhibited the rat granulosa cell viability, increased apoptosis through caspase‐3 activation and Bcl‐2‐associated x protein (BAX) expression, stimulated steroid hormone secretion, and induced the expression of key enzymes in progesterone expression and sex hormone receptors 86‐88 …”
Section: Effects Of Phthalate On Granulosa Cellsmentioning
confidence: 99%